Familial fictions: families and food, convenience and care. (12th November 2018) - Jackson, Peter
Abstract : Purpose: The purpose of this paper is to explore the way diverse family forms are depicted in recent TV advertisements, and how the ads may be read as an indication of contemporary attitudes to food. It focuses particularly on consumers' ambivalent attitude towards convenience foods given the way these foods are moralised within a highly gendered discourse of "feeding the family". Design/methodology/approach: The paper presents a critical reading of the advertisments and their complex meanings for diverse audiences, real and imagined. The latter part of the paper draws on the results of ethnographically-informed fieldwork in the north of England. Findings: The research highlights the value of food as a lens on contemporary family life. It challenges the conventional distinction between convenience and care, arguing that convenience food can be used as an expression of care. Research limitations/implications: The paper makes limited inferences about audiencing processes in the absence of direct empirical evidence. Originality/value: The paper's value lies in its original interpretation of TV food advertising within the context of contemporary family life and in the novel connections that are drawn between convenience and care.